Faktor – Faktor Yang Mempengaruhi Minat Berwirausaha Mahasiswa Program Studi Manajemen Fakultas Ekonomi Universitas Flores - Nasarius Aban; Gabriel Tanusi (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
This study aims to determine the effect of emotional intelligence, independent attitude and family environment on the interest in entrepreneurship at the University of Flores Management Faculty of Economics. This research is an associative research. The population in this study were students of the Management Study Program of the Faculty of Economics of the University of Flores in the class of 2015-2016 who had passed the entrepreneurship courses of 170 people. Samples taken in this study were 105 respondents, with sampling techniques using simple random sampling. Data collection using questionnaires and interviews, while data analysis was performed using multiple linear regression analysis. The results of multiple regression analysis are Y = 1.060 + 0.594X1 + 0.114X2 + 0.421X3 + e. The coefficient of determination R2 for the variables X1, X2, X3 is 0.675, which means that entrepreneurial interest can be influenced by emotional intelligence, independent attitude and family environment by 67.50% and the remaining 32.50% is influenced by other factors including factors of education, skills, motivation and others. F test results show the value of Fcount> Ftable (28.442> 2.69) with a significant level of 0.000 <0.05 meaning that there is a positive and significant influence between emotional intelligence, independent attitude and family environment together on the entrepreneurial interest of the Faculty of Management Study Program Students The economy. Partial test results (t) show 1) Emotional intelligence factors have a positive and significant effect on entrepreneurial interest 2) Family environment factors have a positive and significant effect on entrepreneurial interest 3) Independent attitude factor has no positive and significant effect on entrepreneurial interest.